Creating smart, sustainable cities: Results from best practice smart cities and cities in Slovakia - Dominika Šulyová; Milan Kubina (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2022)
In light of current climate change concerns, it is not enough to create only Smart Cities but it is important to create Smart Sustainable Cities. Countries like Slovakia have not been adequately considering these issues as much as they should. Responding to the opportunity to fill a research gap, primary research has been conducted for this article that seeks i) to use results from previous research to compare currently identified elements influencing the development of a sustainable Smart City concept in Slovakia with best practice cities around the world; and ii) to identify those elements that have achieved a statistically significant correlation with the conceptualisation of Smart Cities in Slovakia. Research data were collected through sociological interrogation, processed in a statistical programme and subsequently evaluated. The findings point to key elements in developing Smart Cities such as trust, state support and adapting to change. The main output is a general model for conceptualising a Smart City. It can be utilised by strategic city management, fellow researchers and residents of a city implementing it in their own practices. The model reflects social, environmental, technological and managerial aspects. Further research into the model and subsequent verification are planned in future.
Keywords: R11; Q01; O13; Q56; 330; Sustainable development; Smart Cities; Climate change; Urbanization; Limited resources; Slovakia; Technology